Blended learning: Adoption pattern of online classrooms in higher education - Kholid Haryono; Almed Hamzah (Institute of Advanced Engineering and Science, 2023)
This study aimed to describe the patterns of technology usage. Specifically, on the implementation of blended learning (BL) in higher education institutions. The case study explores usage patterns, influencing factors, and success factors. The data sources came from the Google Classroom log activity of 35 departments, consisting of five vocational programs, 28 undergraduate programs, and two professional programs in a university for three years with an average in a semester. A method called the customer window quadrant (CWQ) was utilized to analyze the pattern. In addition, a questionnaire was deployed to measure the teacher’s satisfaction with using the Google Classroom in a blended learning setting. The results show two dominant activities in Google Classroom, namely assigning tasks and quizzes. For the quiz, there were two popular question types, i.e., multiple-choice and short answers questions. The activity of using the Google Classroom has doubled in the three years. Assigning tasks to projects becomes the task in the Google Classroom. The usage patterns of Google Classroom are based on the level of importance. There are three activities considered the most important, namely creating class, topic, and material course. Moreover, the most influencing factors are stability, convenience, simplicity, velocity, and reliability.